Intravenous fluid rate for reduction of cesarean delivery rate in nulliparous women: a systematic review and meta‐analysis. (27th March 2017) - Ehsanipoor, Robert M.; Saccone, Gabriele; Seligman, Neil S.; Pierce‐Williams, Rebecca A.M.; Ciardulli, Andrea; Berghella, Vincenzo
Abstract: Introduction: The National Institute of Child Health and Human Development, American College of Obstetricians and Gynecologists, and Society for Maternal‐Fetal Medicine have emphasized the need to promote vaginal delivery and have offered recommendations to safely prevent primary cesarean delivery. However, there has been limited discussion regarding management of intravenous fluids and other aspects of labor management that may influence mode of delivery. Therefore the aim of our study was to determine whether an intravenous fluid rate of 250 vs. 125 mL/h is associated with a difference in cesarean delivery rate. Material and methods: Searches were performed in MEDLINE, OVID, Scopus, ClinicalTrials.gov, the PROSPERO International Prospective Register of Systematic Reviews, Embase, Web of Science, and the Cochrane Library for randomized controlled trials. We included all randomized controlled trials comparing intravenous fluid rates of 250 vs. 125 mL/h in nulliparous women in spontaneous labor at term with singleton pregnancies at ≥36 weeks. Studies were included regardless of the type of intravenous fluids used and regardless of whether oral intake was restricted during labor. Studies including multiparous women or women whose labor was induced were excluded. The primary outcome was the incidence of cesarean delivery. We planned to assess a subgroup analysis according to type of fluids used and according to restriction of oral fluid intake. Results: Seven trials including 1215 nulliparous women in spontaneous labor at term were analyzed; 593 (48.8%) in the 250 mL/h group, and 622 (51.2%) in the 125 mL/h group. Five studies used lactated Ringer's solution, one used normal saline in dextrose water, and in one study it was unclear which intravenous fluid was used. Women who received intravenous fluids at 250 mL/h had a significantly lower incidence of cesarean delivery for any indication (12.5 vs. 18.1%; RR 0.70, 95% CI 0.53–0.92; seven studies, 1215 participants; I 2 = 0%) and for dystocia (4.9 vs. 7.7%; RR 0.60, 95% CI 0.38–0.97; five studies, 1093 participants; I 2 = 18%), a significantly shorter mean duration of labor of about one hour (mean difference −64.38 min, 95% CI −121.88 to −6.88; six studies, 1155 participants; I 2 = 83%) and a significantly shorter mean length of second stage of labor (mean difference −2.80 min, 95% CI −4.49 to −1.10; 899 participants; I 2 = 22%) compared with those who received intravenous fluid at 125 mL/h. No differences were found in the other secondary outcomes. There were no maternal or perinatal deaths and only one woman, in the 125 mL/h group, developed pulmonary edema. The findings persisted regardless of the type of intravenous fluid used. No significant reduction in the incidence of cesarean delivery was demonstrated in women with unrestricted oral intake; however, this was limited to only two studies evaluating 254 women. Conclusions: Our findings provide evidence that the duration of labor in low‐risk nulliparous women may be shortened by a policy of intravenous fluids at a rate of 250 mL/h rather than 125 mL/h. A rate of 250 mL/h seems to be associated with a reduction in the incidence of cesarean delivery compared to 125 mL/h. The number needed to treat to prevent one cesarean delivery is 18 women. Our data support increased hydration among nulliparous women in labor when oral intake is restricted. Further study is needed regarding risks and benefits of increased hydration among women with unrestricted oral intake, those undergoing induction of labor, and those with medical comorbidities.